Acceptance, nutritional content, and shelf life of cookies based on millet flour as a functional food - Anggraini, Putri Dwi Kasih; Salam, Abdul; Wahiduddin, Wahiduddin (Technium Social Sciences Journal, 2021)
The purpose of this study was to determine the acceptability, nutritional content, and shelf life of cookies based on millet flour as a functional food. This type of research is a laboratory-based descriptive. Formulation cookies flour of millet is distinguished by the addition of flavorings nature of which includes millet flour cookies without additional flavorings (F1), banana flavor millet flour cookies (F2), spice flavor millet flour cookies (F3) and chocolate flavor millet flour cookies (F4). Data collection procedure was carried out by hedonic test on untrained panelists consisting of men and women aged 18-40 years as many as 25 panelists, then the selected formulations were analyzed for nutritional content and shelf life. Data were analyzed using the Kruskal-Wallis analysis method and continued with the Mann-Whitney test if the treatment had a significant effect. The panelists' acceptance showed that the formulation of millet flour cookies had no significant effect (p>0.05) on the color, taste, aroma, texture and overall cookies. The F1 cookies formula without the addition of flavoring has the highest average value of the other formulas, which is 4.16 with the preferred category. The results of the proximate test on the selected cookies include water content 6.1%, ash 2.14%, protein 8.38%, fat 30.38%, carbohydrates 53.0%, fiber 2.22%, and total energy 518.98 kcal. The shelf life of cookies using the Arrhenius approach is 14 days at a temperature of 250C, 370C, and a temperature of 440C with the results respectively 134.81 days (4.5 months), 79.18 days (2.6 months) and 59.14 days (1.9 months). While the results of the total microbial test showed that there was a decrease in total microbes in millet flour cookies stored in an incubator at 250C, 370C, and 440C for 4 weeks of storage, respectively 2.05 x 102, 1.05 x 102, and < 4 0.0 x 101, still meets the standard of SNI 01-2973:2011 with a maximum of 1 x 104 colonies/gram. Based on the results of the study, millet flour cookies can be enriched with food sources of protein and fiber so that it can increase the nutritional value of cookies as an additional food.